Aspectos econômicos e socioambientais do Corpo de Bombeiros Militar do Pará: visão sistêmica da ausência de um sistema de informação de custos - CARDOSO, Von Kleber Tadaiesky (Universidade Federal do Pará, 2024)
The dissertation addresses the challenge faced by the Military Fire Department of the State of Pará (CBMPA) in improving the management of its resources in a context marked by significant economic and social challenges in the State of Pará. The region, affected by the exploitation of its natural resources, demands a sustainable approach, emphasizing the need for an efficient Cost Information System (CIS) in the CBMPA. The research identifies a critical gap in resource management due to the absence of a CIS, which negatively impacts the performance and quality of services provided by the corporation. Grounded in the theoretical framework of Accounting Science, the dissertation examines different functions of accounting information in public entities and the importance of systemic cost management analysis. The adopted methodology includes exploratory descriptive research, with data collection conducted through a literature review and a survey with 15 CBMPA employees in the areas of management and planning. The main results revealed that 46.7% of the employees have limited knowledge in accounting, financial, and budgetary areas, and 63.6% report that the available cost information is fragmented and lacks an adequate CIS. Additionally, a significant challenge identified is holding managers accountable for the implementation of the CIS. The research discusses the importance of a CIS for improving the CBMPA's resource management, emphasizing the need for employee training and information integration for effective decision-making. It also highlights how a CIS can contribute to sustainability in the Amazon and enhance public management. In conclusion, the dissertation proposes a CIS model adapted to the organizational structure of the CBMPA and regional specificities. The objective is to map and measure the corporation's costs efficiently, providing valuable information to assist in the planning and execution of public policies, including the Multi- Year Plan (PPA), the Budgetary Guidelines Law (LDO), and the Annual Budget Law (LOA). The implementation of an efficient CIS is seen as fundamental for effective and sustainable management of the CBMPA.